Adverse Childhood Experience as a Risk Factor for Developing Type 2 Diabetes among the Jazan Population: A Cross-Sectional Study - Omar Oraibi; Ali T. Ghalibi; Mohammed O. Shami; Meshal J. Khawaji; Khalid A. Madkhali; Abdulrahman M. Yaseen; Sultan M. Hakami; Nirmin H. Alhazmi; Khulud H. Mahla; Marwah A. Qumayri; Khalid A. Majrashi; Abdulrahman Hummadi; et al. (MDPI AG, 2023)
Background: Adverse Childhood Experiences (ACEs), such as childhood abuse, neglect, and family dysfunction, prevent appropriate emotional, behavioral, and physical development. They are also a major public health issue, and have been debatably linked to chronic diseases, including type 2 diabetes mellitus (T2DM). T2DM is highly prevalent in Saudi Arabia, and various theories have been raised to explain the epidemiology of diabetes. However, few studies have discussed the relationship between ACEs and T2DM. Thus, we aimed to evaluate the association between ACEs and T2DM in Jazan Province, Saudi Arabia. Methods: This observational, cross-sectional study was conducted using a validated questionnaire distributed among patients with T2DM in a diabetes center. The t-test and Chi-Square test were used for comparison, and the p-value was set at <0.05 for significance. Results: A total of 579 participants were involved in this study, and 303 (52.33%) were female. Among the included participants, 45.25% were diagnosed with T2DM. About 28.71% of participants with diabetes experienced verbal abuse, 16.09% experienced physical abuse, and 30.91% reported that parents beat them. Additionally, 1.58% of participants with diabetes reported living with a family member who abused substances, 8.83% believed that no one would take them to the doctor even if essential, 12.62% of participants with diabetes felt that no one would protect them, and 23.03% reported that they felt no one in their family loved them. All reported ACEs were significantly associated with a high risk of T2DM (p < 0.05), and the more frequent the ACEs, the more the risk of T2DM (p = 0.0001). Conclusions: This study indicated that ACEs are significantly associated with the development of T2DM, and the risk increases with the frequency of ACEs, which aligns with other studies. Further national studies are required to understand how ACEs could contribute to T2DM, and preventive interventions in childhood must be considered to reduce the burden of T2DM.